Health Status, Living Arrangements, and Service Use at 100: Findings From the Oporto Centenarian Study - Ribeiro, Oscar (2016)
This paper describes the sociodemographic characteristics, health status, and service use of centenarians living in the community and centenarians residing in an elder care facility/nursing home and examines their main differences. Participants were 140 centenarians from the population-based Oporto Centenarian Study (Mage = 101.2; SD = 1.6). Main findings revealed that the majority of the centenarians lived at home with their family members (57.9%). Increased health care needs, living alone, and family caregiving constraints were the most common reasons for entering a nursing home. Community-dwelling centenarians were cared for mostly by their children and were less dependent and in better cognitive health than those who resided in a nursing home. Differences were found in the pattern of health service use according to the centenarians' residence, ability to pay medical expenses, and dependency level. Findings highlight the need for an accurate assessment of caregiving support systems, particularly family intergenerational duties, and of the factors constraining the access and use of health and social services. Policy makers may be guided by the insights gained from this research and work toward improvement of support options and removal of barriers to service access.